E-Administration and the reengineering of the justice service in Algeria in the context of digital transformation - Ismail, Saihi (The International tax journal, 2026)
This study examines the role of electronic administration in modernizing the justice sector in Algeria within the context of digital transformation. It highlights the main achievements accomplished and the challenges that continue to hinder the establishment of an effective digital justice system. The study adopts a descriptive-analytical approach to assess the current state of justice modernization in Algeria, with a particular focus on its technical and organizational dimensions. The findings indicate that electronic administration has contributed to reducing procedural delays, improving transparency in judicial operations, enhancing the efficiency of case management, and facilitating litigants’ access to judicial services. However, the modernization process still faces several challenges, most notably the limited integration between information systems, the need for further capacity-building and training of human resources, cybersecurity concerns and data protection issues, as well as certain organizational and technical constraints related to infrastructure.